Fact sheets on the European Union (Luxembourg, 2009)
"So what's it about, this 'EU', this European Union that half a billion of us live in? You will find the answer in this book and its accompanying CD-ROM in 21 languages. Explanations, just in the right dose - not too superficial but not into every little juridical detail either - and best of all: In time for the European Parliament elections taking place at the beginning of June. The 165 fact sheets cover six main areas: How the European Union works, Citizens’ Europe, The internal market, Common policies, Economic and monetary union and The EU’s external relations. Everything you need to know in order to vote in June - because you will vote, won't you?!"